Primary cell culture from fin explants of Labeo rohita (Ham.) - Rathore, Gaurav; Kumar, Gokhlesh; Swaminathan, T Raja; Sood, Neeraj; Singh, Vijay; Abidi, Rehana; Lakra, W S (Indian Journal of Fisheries, 2011)
The study reports a successful development of primary cell culture from fin explants of labeo rohita and subsequent subculture up to eight passages. Explant tissues of fin were seeded and incubated at 30Â°C in DMEM supplemented with 10% FCS. On day 5 of seeding, the differentiation of the cells was visible and a complete monolayer was obtained on day 20. A cell count of 2 X 106 cells was sufficient to produce monolayer in 5 days on 8th passage. These encouraging results are indicative of a high probability of developing a cell line from the fin tissue of L. rohita